2011
DOI: 10.2174/187221311797264937
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids: Molecular Mechanisms of Action as Anti- Inflammatory Agents

Abstract: Flavonoids are a large group of polyphenolic compounds, which are ubiquitously expressed in plants. They are grouped according to their chemical structure and function into flavonols, flavones, flavan-3-ols, anthocyanins, flavanones and isoflavones. Many of flavonoids are found in fruits, vegetables and beverages. Flavonoids have been demonstrated to have advantageous effects on human health because their anti-allergic, anti-inflammatory, anti-platelet aggregation, anti-tumor and anti-oxidant behavior. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 0 publications
1
138
0
3
Order By: Relevance
“…Flavonoids can be categorized into six major subclasses based on their range and structural complexity: flavonols, flavones, flavan-3-ols, flavanones, anthocyanins, and isoflavones. Flavonols mainly exist in onions, broccoli, tea, and various common fruits; flavones are common in aromatic herbs, celery, and chamomile tea; flavan-3-ols are present in cocoa, red wine, grapes, apples, green tea, and other fruits; flavanones can be found in oranges and other citrus fruits; anthocyanidines are abundant in colored berries, black currants; and isoflavones are found in soy food (22,23). In fact, our previous study revealed that flavonols and flavones, but not the total flavonoids, flavan-3-ols, flavanones, or anthocyanins, reduce breast cancer risk (24).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids can be categorized into six major subclasses based on their range and structural complexity: flavonols, flavones, flavan-3-ols, flavanones, anthocyanins, and isoflavones. Flavonols mainly exist in onions, broccoli, tea, and various common fruits; flavones are common in aromatic herbs, celery, and chamomile tea; flavan-3-ols are present in cocoa, red wine, grapes, apples, green tea, and other fruits; flavanones can be found in oranges and other citrus fruits; anthocyanidines are abundant in colored berries, black currants; and isoflavones are found in soy food (22,23). In fact, our previous study revealed that flavonols and flavones, but not the total flavonoids, flavan-3-ols, flavanones, or anthocyanins, reduce breast cancer risk (24).…”
Section: Discussionmentioning
confidence: 99%
“…An inverse association between levels of physical activity and the risk of colon cancer has been one of the most consistently observed (Colbert et al, 2001, Colditz et al, 1997) with a recent meta-analysis demonstrating that physically active individuals had a 20-30% lower risk of colon cancer compared to less active individuals (Wolin et al, 2009). The mechanisms by which physical activity reduces the risk of CRC are not yet fully understood, however, it may be in part due to a reduction in systemic inflammation which is largely mediated through the inhibition of COX-2 (Chan and Giovannucci, 2010 (Marzocchella et al, 2011).…”
Section: Moderation Of the Inflammatory Response In Colorectal Cancermentioning
confidence: 98%
“…In particular, the flavonoids are polyphenol which structure consisting of 2 aromatic rings bound together by 3 carbon atoms that form an oxygenated heterocycle, which give colors to vegetables, fruits, grains, leaves, flowers. Their effects included the reduction of the activities of the arachidonic acid metabolizing enzymes (phospholipase A2, cyclooxygenase, lipoxygenase), inhibition of proinflammatory cytokines (IL-1b, IL-2, IL-6, TNF-α), modulation of NO synthase pro-inflammatory gene expression, and beneficial immunomodulatory effects [27].…”
Section: Dietary Vs Supplemental Antioxidants: Same Effectiveness?mentioning
confidence: 99%